TINJAUAN HUBUNGAN HUKUM PERJANJIAN LEASING - Silvi Triadita Sari; Arief Suryono (Jurnal Privat Law, 2021)
AbstractThis article aims to understand the the construction of legal relation of parties in motor vehicle leasing agreement. This study was normative law research that was prescriptive and applied in nature.  The approach used statute approach with secondary data source supported with primary data as supporting data. Techniques of collecting data used were literature studies and field studies. Furthermore, technique of analyzing data used was deductive method.  Considering the result of research analysis, it could be concluded that the construction of legal relation in leasing agreement did not meet the fourth requirement of legitimate agreement based on Article 1320 of KUHPerdata (Civil Code). Leasing agreement is in contradiction with Article 65 clause (2) of Law Number 22 of 2009 about Traffic and Road Transportation in the case of leasing object property juridically based on the certificate of ownership of the motor vehicle (BPKB). Although leasing agreement is based on the principle of contract freedom, its existence may not be in contradiction with the law, morality, and public orderliness as governed in Article 1337 of KUHPerdata Thus, the legal consequence of agreement should be void for the sake of law. Particularly for motor vehicle leasing in leasing agreement, the parties should agree to override the Article 65 clause (2) of Law Number 22 of 2009 just like the parties overriding Article 1266 of KUHPerdata to lessee in agreement. AbstrakArtikel ini bertujuan untuk mengetahui konstruksi hukum para pihak dalam perjanjian leasing kendaraan bermotor. Penelitian hukum ini termasuk jenis penelitian hukum normatif yang bersifat preskriptif dan terapan. Pendekatan yang digunakan adalah pendekatan perundang-undangan (statute approach) dengan sumber data sekunder yang ditunjang dengan data primer sebagai data pendukungnya. Teknik pengumpulan data menggunakan studi kepustakaan dan studi lapangan. Selanjutnya teknik analisis data menggunakan metode deduksi. Berdasarkan hasil analisis penelitian, dapat diambil kesimpulan bahwa konstruksi hukum perjanjian leasing tidak memenuhi syarat sahnya perjanjian yang keempat berdasarkan Pasal 1320 KUHPerdata. Perjanjian leasing bertentangan dengan Pasal 65 ayat (2) Undang-undang No. 22 Tahun 2009 tentang Lalu Lintas dan Angkutan Jalan dalam hal hak milik objek leasing secara yuridis berdasarkan BPKB. Meskipun perjanjian leasing didasarkan pada asas kebebasan berkontrak, namun keberadaannya tidak boleh bertentangan dengan undang-undang, kesusilaaan, maupun ketertiban umum seperti yang diatur dalam Pasal 1337 KUHPerdata. Sehingga akibat hukumnya perjanjian tersebut seharusnya batal demi hukum. Khusus untuk leasing kendaraan bermotor dalam perjanjian leasing, para pihak seharusnya sepakat untuk mengesampingkan Pasal 65 ayat (2) Undang-undang No. 22 Tahun 2009 sebagaimana para pihak mengesampingkan Pasal 1266 KUHPerdata bagi lessee dalam perjanjian.